The Metamorphosis of Amphibian Toxicogenomics - Helbing, Caren (Frontiers in Genetics, 2012)
Amphibians are important vertebrates in toxicology often representing both aquatic and terrestrial forms within the life history of the same species. Of the thousands of species, only two have substantial genomics resources: the recently published genome of the Pipid, Xenopus (Silurana) tropicalis, and transcript information (and ongoing genome sequencing project) of Xenopus laevis. However, many more species representative of regional ecological niches and life strategies are used in toxicology worldwide. Since Xenopus species diverged from the most populous frog family, the Ranidae, ~200 million years ago, there are notable differences between them and the even more distant Caudates (salamanders) and Caecilians. These differences include genome size, gene composition, and extent of polyploidization. Application of toxicogenomics to amphibians requires the mobilization of resources and expertise to develop de novo sequence assemblies and analysis strategies for a broader range of amphibian species. The present mini-review will present the advances in toxicogenomics as pertains to amphibians with particular emphasis upon the development and use of genomic techniques (inclusive of transcriptomics, proteomics, and metabolomics) and the challenges inherent therein.